Is there a wage curve with regional real wages? - Bartlomiej Rokicki; Uwe Blien; Geoffrey Hewings; Van Phan thi Hong (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
Do wages react to regional unemployment, as proposed by the theory behind the regional wage curve, if regional price differences are taken into account? This paper applies regional price indexes to assess the wage curve, whereas in the literature only nominal wages are used for wage curve regressions. In order to test the impact of regional prices on the wage curve we apply a variety of methodological approaches. With individual data from the US Census and the Polish Labor Force Survey we find a wage curve. However, in both countries, the local unemployment elasticity and spatial spillovers decrease significantly once regional price deflators are applied. – – Reagieren die Löhne auf regionale Arbeitslosigkeit, wie es die Theorie hinter der regionalen Lohnkurve behauptet, wenn regionale Preisunterschiede berücksichtigt werden? In diesem Papier werden regionale Preisindizes zur Beurteilung der Lohnkurve verwendet, während in der Literatur nur Nominallöhne für Lohnkurvenregressionen verwendet werden. Mit Individualdaten aus der US-Volkszählung und der polnischen Arbeitskräfteerhebung finden wir eine Lohnkurve. In beiden Ländern nehmen jedoch der Lohneffekt der Arbeitslosigkeit und ihre räumlichen Auswirkungen erheblich ab, sobald regionale Preisdeflatoren angewendet werden.
Keywords: C26; J30; J60; 330; Wage Curve; Spatial Spillovers; Regional Price Index; Regional Labor Markets